1991
DOI: 10.1159/000217690
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HLA Class I and Class II in Gastric Carcinoma in Relation to Pathologic Stage

Abstract: The expression of HLA class I and II antigens was studied in 41 patients with gastric cancer and in 2 normal stomachs. The normal gastric epithelia were diffusely stained for class I antigens. No staining was observed for class II. In gastric cancer an overall reduction in staining was observed, which was related to the degree of tumor penetration through the gastric wall. In tumors which penetrated the mucosa and submucosa only, 80–90% of tumor cells were stained for class I, as well as the normal areas surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…With regard to gastric cancer, only a few studies investigated the expression of HLA-I [21][22][23][24][25]. Ferron et al [21] analyzed the expression of HLA-I and II antigens on gastric carcinomas and autologous mucosa by cryopreserved tissue samples, and they reported that the autologous mucosa lacked the expression of HLA antigens before becoming malignant.…”
Section: It Is Generally Accepted That An Anticancer Immune Reaction mentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to gastric cancer, only a few studies investigated the expression of HLA-I [21][22][23][24][25]. Ferron et al [21] analyzed the expression of HLA-I and II antigens on gastric carcinomas and autologous mucosa by cryopreserved tissue samples, and they reported that the autologous mucosa lacked the expression of HLA antigens before becoming malignant.…”
Section: It Is Generally Accepted That An Anticancer Immune Reaction mentioning
confidence: 99%
“…Ferron et al [21] analyzed the expression of HLA-I and II antigens on gastric carcinomas and autologous mucosa by cryopreserved tissue samples, and they reported that the autologous mucosa lacked the expression of HLA antigens before becoming malignant. Klein et al [22] reported that reduced HLA-I expression in gastric cancer, which correlated with deeper cancer invasion. Their study has analyzed expression of the entire HLA-I complex using polyclonal antihuman b2 microglobulin.…”
Section: It Is Generally Accepted That An Anticancer Immune Reaction mentioning
confidence: 99%
“…These alterations include imbalances of expression between the different loci at the MHC, and either a decreased or increased expression of class I MHC-encoded antigens (Goodenow et al, 1985;Festenstein & Garido, 1986;Garcia-Espejo et al, 1986;Blackmore ef al., 1987;Festenstein, 1987). In a variety of human tumours, reduced expression of HLA class I has been reported (Kabawat et al, 1983;Doyle et al, 1985;Lopez Nevot et al, 1986) and in some tumours this attenuation was correlated with the degree of tumour differentiation (Eyal etal., 1990), aggressiveness (Klein et al, 1990b), invasiveness (Klein et al, 1991), and survival (Levin et al, 1991a).…”
Section: Introductionmentioning
confidence: 99%
“…MHC class I antigens, which are present on all nucleated cells, are required for the lysis of malignant cells by cytotoxic T cells [23], In experimental tumors, reduced expres sion of MHC class I antigens has been de scribed, and this attenuation correlated di rectly with the ability of the tumor cells to avoid immune rejection and develop in im munocompetent hosts [24]. In several human tumors, reduced expression of HLA class I antigens has been described [25][26][27], which correlated with the degree of tumor aggres siveness [25], differentiation [26], and surviv al [27,28], (32-Microglobulin (p^M), which forms the light chain of the HLA class I molecule, is an 11,800-dalton, single-chain polypeptide and is present on the surface of the cells as part of the HLA complex [29]. When the HLA com plex is metabolized, the P2M sheds into the extracellular fluid and can be measured in the serum.…”
Section: Introductionmentioning
confidence: 99%